2016
DOI: 10.1016/j.plaphy.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on the characterization of aldonolactone oxidoreductases

Abstract: l-Ascorbic acid (ascorbate, AsA, vitamin C) is essential for animal and plant health. Despite our dependence on fruits and vegetables to fulfill our requirement for this vitamin, the metabolic network leading to its formation in plants is just being fully elucidated. There is evidence supporting the operation of at least four biosynthetic pathways leading to AsA formation in plants. These routes use d-mannose/l-Galactose, l-gulose, d-galacturonate, and myo-inositol as the main precursors. This review focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 112 publications
1
19
0
Order By: Relevance
“…However, unlike MsGulLO, MsGLDH was predicted to be a mitochondrial protein, containing no signal peptide but a FAD-binding motif in the N terminus. This prediction is in agreement with plant GLDHs being localized in the mitochondria ( Aboobucker and Lorence, 2016 ). MsGLDH had an instability index (II) of 44.97, which indicated that it is not theoretically stable.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…However, unlike MsGulLO, MsGLDH was predicted to be a mitochondrial protein, containing no signal peptide but a FAD-binding motif in the N terminus. This prediction is in agreement with plant GLDHs being localized in the mitochondria ( Aboobucker and Lorence, 2016 ). MsGLDH had an instability index (II) of 44.97, which indicated that it is not theoretically stable.…”
Section: Resultssupporting
confidence: 90%
“…The full amino acid sequence of MsGulLO was deduced from the cDNA sequence, and subjected to a Pfam search which revealed an ALO family domain at positions 375−520 ( E -value: 5.6e −13 ) and an FAD binding domain at positions 2−133 ( E -value: 6.3e −22 ). However, in common with other plant GulLOs, MsGulLO doesn’t have a FAD-binding motif in its N terminus ( Leferink et al, 2008 ; Aboobucker and Lorence, 2016 ). The mature MsGulLO protein had a neutral isoelectric point of 6.72, and a predicted molecular mass of 61,962.52 Da which is consistent with the 2-DE results ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, M. tuberculosis GulLDH had higher activity when phenazine methosulfate was used as an electron acceptor similar to the findings of Mapson and Breslow [16]. No flavin prosthetic group is found when aldonolactone oxidoreductases—known to have a covalent FAD but not non-covalent FAD—are expressed recombinantly in E. coli [61, 62]. However, no problem with the attachment of the flavin group was experienced when aldonolactone oxidoreductases were expressed in eukaryotic systems [6365].…”
Section: Discussionmentioning
confidence: 74%